Green synthesis of silver nanoparticles using avocado (Persea sp.) peel extract as bioreducing agent: optimization, characterization, stability, and antioxidant activity - Amilatusolihah; Demi Dama Yanti; Abdul Aji; Ahmad Anggraria Jaya Agung; Muhammad Yogi Saputra; M. Rofif Nurfaizi; Neng Tresna Umi Chulsum (Scientific Nexus, 2025)
The increasing demand for naturally derived antioxidants has driven interest in green synthesis of silver nanoparticles as a strategy to combine the bioactive properties of plant metabolites with the unique characteristics of nanomaterials. This study reports the green synthesis of AgNPs using avocado peel extract as a bioreducing and stabilizing agent, with optimization of synthesis parameters, physicochemical characterization, colloidal stability evaluation, and antioxidant activity assessment. Optimum synthesis conditions were established at 2 mM AgNO₃, 60 °C, and 60 min reaction time, yielding a characteristic surface plasmon resonance peak at 420 nm. FTIR analysis confirmed the involvement of O–H, C–H, C=C aromatic, and C–O functional groups derived from phenolic and flavonoid compounds in the reduction and nanoparticle stabilization processes. Particle size analysis revealed an average hydrodynamic diameter of 83.5 nm with a polydispersity index of 0.287. Stability studies over six months demonstrated that refrigerated storage at 4 °C in the dark produced the most stable absorbance profile. Antioxidant evaluation by the DPPH radical scavenging assay yielded IC₅₀ values of 126.04 µg/mL for AgNPs and 133.11 µg/mL for the extract, both classified as moderate antioxidant agents. These findings establish avocado peel as a promising, sustainable bioresource for the fabrication of antioxidant-active AgNPs.